AFFIRMING WIBU’S STEREOTYPES THROUGH YOUTUBE VIDEOS - Junianto, Iqbal Eka; Tambunan, Shuri Mariasih Gietty (UI Scholars Hub, 2024)
In 2022, based on Google Trends tools, Indonesia is ranked third as the country with the most searches related to Japanese anime. Wibu is a term that refers to someone who is outside Japan but likes and even tends to be obsessed with the culture of that country. This research aims explore how stereotypes of Wibu in Indonesia are constructed by digital media, specifically YouTube. Research findings show that Wibu in Indonesia is stereotyped as